Evaluation of Seaweed Meal and Konjac Glucomannan Mixture as Feed Ingredients in Largemouth Bass Micropterus salmoides - Yan-Bo Cheng; Dan Wu; Liang Gao; Shun Rong; Guo-Huan Xu; Xu-Fang Liang (Fishes)
To address the negative effects of high-starch diets on largemouth bass (LMB), this study evaluated the feasibility of using a Gracilaria lemaneiformis-konjac glucomannan mixture (GKM, 2:1) as a substitute for strong flour (SF). Four iso-nitrogenous and iso-lipid diets were formulated: a control (15% SF; GK00) and three other diets replacing 33.3% (GK05), 66.7% (GK10), or 100% (GK15) of SF with GKM. Each diet was randomly administered to triplicate tanks of fish (10.49 ± 0.232 g) for a 10-week feeding trial. Results showed that the GKM inclusion groups significantly improved the fish survival and feed intake. Fish in GK05 and GK10 groups exhibited significantly higher final body weight, weight gain, and specific growth rate than the GK00 group, while GK15 showed no significant increase in these metrics. There was no impairment in protein, lipid, phosphorus, and energy retention efficiency in the GK05 and GK10 groups compared to those of the GK00 group. Apparent digestibility for feed dry matter, protein, lipid, phosphorus, and the 16 amino acids was not decreased in the GK05 and GK10 groups relative to the GK00 group. In addition, this study revealed reduced phosphorus waste per kilogram of weight gain in GK05 and GK10. In conclusion, these findings position GKM as a sustainable alternative to SF in feed for LMB.